“Science is nothing but perception” (Tht. 151e2-3). On the role of perception in the process of knowledge - Eustacchi, Francesca (Revista Archai, 2025)
In the first part of the Theaetetus, Plato engages with the Protagorean position, interpreting the homo mensura maxim on a sensory basis. The dialogue aims to investigate and define the nature of knowledge, initially identified with perception. This study offers an analytical examination of the discussion Socrates conducts with Theodorus and Theaetetus, two mathematicians who convey Protagoras’s thought. It highlights the theoretical approach through which Plato, on the one hand, directs precise criticisms at the sophist’s view, demonstrating the impossibility of considering individual human perception as a cognitive foundation, and on the other, acknowledges its contribution to better defining the role of perception in knowledge. When considered in relation to Letter VII, this discussion proves useful in clarifying a central aspect of Plato’s complex epistemological vision.